2014
DOI: 10.1111/bjd.12806
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of bullous pemphigoid in Singapore: risk factors and causes of death in 359 patients seen at the National Skin Centre

Abstract: SummaryBackground Bullous pemphigoid (BP) is the most common autoimmune-mediated subepidermal blistering skin disease and is associated with significant morbidity and mortality. Objectives To determine the 3-year mortality rate, risk factors and causes of death in patients with BP in Singapore, compared with the general population. Methods We conducted a retrospective cohort study of all newly diagnosed patients with BP seen at the National Skin Centre from 1 April 2004 to 31 December 2009. Demographic and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
117
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(132 citation statements)
references
References 43 publications
11
117
2
2
Order By: Relevance
“…The most recent study on patients from Singapore reported a higher mortality rate (26.7%) than our study; however, the median age of their study population was slightly older (75.7 years) than ours (73 years). 21 A summary of 1-year mortality rate in BP cohorts from recently published studies is shown in Table V. This study was designed to assess the overall survival of patients with BP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most recent study on patients from Singapore reported a higher mortality rate (26.7%) than our study; however, the median age of their study population was slightly older (75.7 years) than ours (73 years). 21 A summary of 1-year mortality rate in BP cohorts from recently published studies is shown in Table V. This study was designed to assess the overall survival of patients with BP.…”
Section: Discussionmentioning
confidence: 99%
“…For all age groups, the rate of observed deaths was higher than that expected for the general population, particularly in BP patients who were 60 to 80 years of age. Several cohort studies have reported that patients with BP have increased mortality, compared with ageadjusted general populations, 17,[19][20][21][22] with the exception of 1 study conducted in the United States, 15 which showed that the morality rate of patients with BP was not higher than that of the general population. Because the US study was a retrospective cohort study, the study might have selection bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this age-specific trend in sex difference is unexplained. Although the female sex has been associated with a slightly increased incidence of BP, studies have not discovered the female sex to be associated with mortality rate or relapse rates of BP (Cai et al, 2014, Fichel et al, 2014). Future research regarding age-specific sex predominance of BP, as well as its epidemiology in America, Africa, and Oceania, may be implicated.…”
Section: Epidemiology and Etiologymentioning
confidence: 99%
“…Previous studies reported an incidence of BP ranging from 2.5 to 42.8 cases per million per year [2, 11, 14, 23]. BP has been reported to be significantly associated with mortality, with morality rates ranging from 6 to 41% within the first year after diagnosis [1, 36, 12, 15, 22, 27, 29, 30, 32]. BP patients also have increased mortality compared with their age and sex-matched controls in the general population [24, 12, 14].…”
Section: Introductionmentioning
confidence: 99%